THE INFLUENCE OF SOCIO-DEMOGRAPHIC CHARACTERISTICS ON AGRI-FOOD CONSUMPTION BEHAVIOR IN THE CONTEXT OF EUROPEAN POLICIES - Ruxandra-Eugenia POP (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the global context of sustainable development and facilitating the transition from production and consumption models to more sustainable ones in relation to environmental resources but also to the health of the population, consumer behavior on agri-food markets is represented in most policies and directions of action. The 2030 Agenda for Sustainable Development, the European Green Deal and the Farm to Fork Strategy, as well as the European directives on various characteristics of agricultural production, transposed at national level, are just some of the official reference documents for this research subject. The paper aims to identify optimal solutions for the effective promotion of sustainable agri-food product behavior. In this approach, one of the key specific objectives is outlined, which is to determine the influence that some socio-demographic characteristics exert within the purchasing process on reference markets, at the level of consumers in Romania. In order to identify the synergy between the independent and dependent variables, a series of marketing studies were conducted at the level of 4 product groups, namely nuts, whole grains, berries and green vegetables. In order to achieve the main goals of this work, specific methods were used, both from qualitative and quantitative research field. To determine the current context at the level of the studied markets, several publications were analyzed (previous studies related to the topic, official documents included in European legislative framework, statistical data published in official databases (Eurostat, FAO, NIS). Also, among the Romanian consumers, a questionnaire was applied, in order to determine their behavior on nuts, whole grains, berries and green vegetables markets. The research results interpretation highlights a trend of consumers towards a balanced lifestyle, and a relevant awareness degree regarding the benefits of introducing the mentioned categories into the daily diet. However, it is also observed the link between the socio-demographic characteristics of respondents (income level, professional status and gender) and the consumption behavior. Consumers perception, childhood habits, the awareness degree cultural factors should also be mention as important independent variables related to the research topic.